Low clinical performance of the Isopollo COVID-19 detection kit (M Monitor, South Korea) for RT-LAMP SARS-CoV-2 diagnosis: A call for action against low quality products for developing countries. (March 2021) - Freire-Paspuel, Byron; Garcia-Bereguiain, Miguel Angel
Highlights: "Isopollo COVID19 detection kit" for RT-LAMP based SARS-CoV-2 diagnosis show a poor clinical performance with sensitivity of 61.9. "Isopollo COVID19 detection kit" presented a good sensitivity only for viral loads above 100.000 copies/mL of sample. Emergency use authorization at country of origin should be mandatory for SARS-CoV-2 RT-PCR diagnosis kits prior to importation to developing countries like Ecuador. Abstract: Background: Multiple molecular kits are available for the diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) worldwide, with many lacking proper clinical evaluation due to the emergency caused by the coronavirus disease 2019 (COVID-19) pandemic, particularly in developing countries. Methods: This study was conducted to evaluate the clinical performance of the Isopollo COVID-19 detection kit (M Monitor, South Korea) for reverse transcription loop-mediated isothermal amplification (RT-LAMP) SARS-CoV-2 diagnosis, using the SARS-CoV-2 reverse transcription polymerase chain reaction (RT-PCR) protocol as the gold standard. Results: A total of 220 clinical samples were included in the study; 168 samples were SARS-CoV-2-positive and 52 samples were SARS-CoV-2-negative according to the SARS-CoV-2 RT-PCR protocol. For the Isopollo COVID-19 detection kit, only 104 out of 168 samples were SARS-CoV-2-positive. This result shows a low clinical performance, with sensitivity of 61.9% for the evaluated RT-LAMP assay. Conclusions: Proper clinical performance evaluation studies by regulatory agencies in developing countries such as Ecuador should be mandatory prior to clinical use authorization of SARS-CoV-2 diagnosis kits, particularly when those kits lack either US Food and Drug Administration or country of origin clinical use authorization.